All-solid-state battery and application thereof
By adopting a composite membrane structure in an all-solid-state battery, combining specific chemical compositions and thicknesses, the solid electrolyte membrane has solved the problem of high lithium ion conductivity, electrochemical redox stability and positive and negative electrode compatibility, and improved the circulation of the battery Performance and stability extend the battery life.
Patent Information
- Application Number
- CN202411545107.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
AI Technical Summary
The solid electrolyte membrane in all-solid state batteries is difficult to have the advantages of high lithium ion conductivity, electrochemical redox stability and good compatibility of positive and negative electrodes, which limits the development and application of batteries.
A composite film consisting of a first solid electrolyte layer and a second solid electrolyte layer is adopted, wherein the ionic conductivity of the first solid electrolyte layer is 1×10-4S/cm-1×10-2S/cm, and the second solid electrolyte layer is The ionic conductivity is 1×10-3S/cm-2×10-2S/cm. The stability and compatibility of the membrane are ensured through specific chemical composition and thickness control.
It improves the cycle performance and stability of the battery, extends the service life of the battery, and is adapted to the high-voltage positive electrode, enhancing the safety of the battery.
Smart Images

Figure CN119253023A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to an all-solid-state battery and applications thereof. Background Art
[0002] With the rapid development of electric vehicles and wearable devices, the demand for high-performance lithium-ion batteries is growing. Among them, all-solid-state batteries, as a type of lithium-ion battery, have attracted widespread attention due to their advantages such as high energy density, good safety and strong durability. However, in the actual application of all-solid-state batteries, it is difficult for solid electrolyte membranes to simultaneously have the advantages of good film forming properties, high lithium ion conductivity, excellent electrochemical redox stability and good compatibility between positive and negative electrodes, which limits the development and application of all-solid-state batteries. Summary of the invention
[0003] The present invention proposes an all-solid-state battery and its application. Through the all-solid-state battery and its application provided by the present invention, the solid electrolyte membrane in the all-solid-state battery can have the advantages of high lithium ion conductivity, excellent electrochemical redox stability and good compatibility between positive and negative electrodes, thereby improving the performance of the all-solid-state battery.
[0004] In order to solve the above technical problems, the present invention provides an all-solid-state battery, comprising at least:
[0005] The first solid electrolyte layer is arranged on the positive electrode side of the all-solid-state battery, and the ion conductivity of the first solid electrolyte layer is 1×10 -4 S / cm-1×10 -2 S / cm; and
[0006] The second solid electrolyte layer is arranged on the negative electrode side of the all-solid-state battery, and the ion conductivity of the second solid electrolyte layer is 1×10 -3 S / cm-2×10 -2 S / cm.
[0007] In one embodiment of the present invention, the first solid electrolyte layer includes a first electrolyte, and the chemical formula of the first electrolyte is Li 2+n Zr 1-n M n Cl 6-x-y Br x I y , wherein 0≤n≤0.6, 0≤x≤6, 0≤y≤6, x+y≤6, and M is selected from at least one of V, Cr, Mn, Fe, Co and Ni.
[0008] In one embodiment of the present invention, M is Fe, and the value range of n is 0.01≤n≤0.5.
[0009] In an embodiment of the present invention, the second solid electrolyte layer includes a second electrolyte, and the chemical formula of the second electrolyte is Li a P 1-b T b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, T is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V or Nb, and X is selected from at least one of Cl, Br or I.
[0010] In an embodiment of the present invention, T is selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is 0 < b ≤ 0.1.
[0011] In an embodiment of the present invention, the second solid electrolyte layer includes a second electrolyte, and the chemical formula of the second electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from at least one of Cl, Br or I.
[0012] In an embodiment of the present invention, E is Mg, Q is Cl, and the value range of g is 0.01 ≤ g ≤ 0.1.
[0013] In an embodiment of the present invention, the thickness of the first solid electrolyte layer is 1 μm to 100 μm.
[0014] In an embodiment of the present invention, the thickness of the second solid electrolyte layer is 5 μm to 150 μm.
[0015] The present invention also provides an electronic device including the above all-solid-state battery.
[0016] In summary, the present invention provides an all-solid-state battery and its application, which can endow the solid electrolyte membrane in the all-solid-state battery with the advantages of high lithium ion conductivity, thereby improving the working efficiency of the battery. It can improve the electrochemical oxidation-reduction stability of the solid electrolyte membrane, enabling the electrolyte to effectively resist problems such as oxidation-reduction reactions and unstable electrode interfaces. It can broaden the electrochemical window of the solid electrolyte membrane, enabling the solid electrolyte membrane to be compatible with high-voltage positive electrodes such as lithium-rich manganese-based or lithium nickel manganate, thereby improving the stability of lithium-ion batteries. Moreover, it can improve the cycling performance of the all-solid-state battery and extend the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0018] Figure 1 Schematic diagram of the structure of an all-solid-state battery in one embodiment of the present invention.
[0019] Figure 2 Schematic diagram of the process of preparing the first solid electrolyte layer and the second solid electrolyte layer in one embodiment of the present invention.
[0020] Figure 3 FIG. 5 is a scanning electron microscope image of a solid electrolyte membrane in one embodiment of the present invention.
[0021] Figure 4 This is a graph showing the results of a room temperature cycle performance test on the all-solid-state battery in Example 2 of the present invention.
[0022] Marking Description:
[0023] 10. All-solid-state battery; 11. Positive electrode; 12. Negative electrode; 13. Solid electrolyte membrane; 131. First solid electrolyte layer; 132. Second solid electrolyte layer. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0025] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0026] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] See also Figure 1As shown, the present invention proposes an all-solid-state battery 10, for example, including a positive electrode 11, a negative electrode 12 and a solid electrolyte membrane 13, wherein the solid electrolyte membrane 13 is arranged between the positive electrode 11 and the negative electrode 12, and the solid electrolyte membrane 13, for example, includes a first solid electrolyte layer 131 and a second solid electrolyte layer 132 arranged in a stacked manner, the first solid electrolyte layer 131 is arranged on the side of the positive electrode 11, and the second solid electrolyte layer 132 is arranged on the side of the negative electrode 12. In the all-solid-state battery 10 provided by the present invention, the solid electrolyte membrane 13 can simultaneously take into account the advantages of high lithium ion conductivity, excellent electrochemical redox stability and good compatibility between positive and negative electrodes, thereby improving the cycle performance, stability and safety of the battery. Specifically, the first solid electrolyte layer 131 enables the solid electrolyte membrane 13 to match the high-voltage positive electrode, and the second solid electrolyte layer 132 can provide high lithium ion conductivity and good electrochemical redox stability. In the present invention, the all-solid-state battery 10 is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the type and type of the all-solid-state battery 10.
[0028] See also Figure 1 As shown, in one embodiment of the present invention, the positive electrode 11 includes, for example, a positive electrode active material, a solid electrolyte, a conductive agent, and a binder. Among them, the positive electrode active material is, for example, selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA), and the solid electrolyte is, for example, a halide electrolyte that does not react with the positive electrode active material to generate heat, so as to improve the safety of the battery. The conductive agent is, for example, selected from at least one of conductive carbon black (SuperP), nanocarbon fiber (Vapor-grown carbonfiber, VGCF), acetylene black, carbon nanotubes or graphene. The binder is, for example, selected from at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride, polyethylene oxide, polyamide, polyacrylonitrile, polyacrylate, polyvinyl ether, polymethyl methacrylate, ethylene-propylene-diene terpolymer, polyhexafluoropropylene or styrene-butadiene rubber. The present invention does not limit the mass ratio of the positive electrode active material, the solid electrolyte, the conductive agent and the binder, and the ratio can be selected according to actual needs.
[0029] See also Figure 1 As shown, in one embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, halide electrolytes, for example, Li 2.35 Zr 0.65 Fe0.35 Cl5Br 0.5 I 0.5 The conductive agent includes, for example, SuperP and VGCF, and the mass ratio of SuperP and VGCF is, for example, 1:1, and the binder is, for example, PTFE. The positive electrode active material, the halide solid electrolyte, the conductive agent and the binder are mixed evenly in a mass ratio of, for example, 69:29:1:1, and the positive electrode 11 is obtained by dry pressing.
[0030] See also Figure 1 As shown, in one embodiment of the present invention, the material of the negative electrode 12 is selected from at least one of a metallic lithium negative electrode material, a carbon-based negative electrode material or an oxide negative electrode material, wherein the carbon-based negative electrode material includes, for example, a carbon-based, silicon-based and tin-based material, and the oxide negative electrode material includes, for example, a metal oxide, a metal-based composite oxide and other oxides. In this embodiment, the negative electrode 12 is, for example, metallic lithium.
[0031] See also Figure 1 As shown, in one embodiment of the present invention, the thickness of the solid electrolyte membrane 13 is, for example, 5 μm to 200 μm, and the ionic conductivity is, for example, 1×10 -4 S / cm~2×10 -2 S / cm. The thickness of the first solid electrolyte layer 131 is, for example, 1 μm to 100 μm, and the ionic conductivity is, for example, 1×10 -4 S / cm~1×10 -2 S / cm, the thickness of the second solid electrolyte layer 132 is, for example, 5 μm to 150 μm, and the ionic conductivity is, for example, 1×10 -3 S / cm~2×10 -2 By controlling the thickness of the solid electrolyte membrane 13, the first solid electrolyte layer 131 and the second solid electrolyte layer 132, the cycle performance of the all-solid-state battery 10 can be improved, thereby extending the service life of the battery.
[0032] See also Figure 1 As shown, in one embodiment of the present invention, the first solid electrolyte layer 131 includes a first electrolyte, which is, for example, a halide electrolyte, and can widen the electrochemical window of the solid electrolyte membrane 13, so that the solid electrolyte membrane 13 can adapt to the high-voltage positive electrode. Specifically, the chemical formula of the first electrolyte is, for example, Li 2+n Zr 1-n M n Cl 6-x-y Br x I y, wherein 0≤n≤0.6, 0≤x≤6, 0≤y≤6, x+y≤6, and M is selected from at least one of V, Cr, Mn, Fe, Co, or Ni. Further, M is, for example, Fe, and the value range of n is 0.01≤n≤0.5, and specifically, n is, for example, 0.35. By limiting the type of M element in the first electrolyte and the value range of n, the chemical stability and lithium ion conductivity of the first solid electrolyte layer 131 can be improved.
[0033] See also Figure 1 to Figure 2 As shown, in one embodiment of the present invention, when preparing the first solid electrolyte layer 131, firstly, in an atmosphere of an inert gas such as argon, according to the chemical formula of the first electrolyte Li 2+n Zr 1-n M n Cl 6-x-y Br x I y , after the Li source, Zr source, M source, Cl source, Br source and I source are mixed evenly according to the stoichiometric amount, for example, they are placed in a ball mill for ball milling to obtain the first electrolyte. Wherein, the Li source is, for example, selected from at least one of LiCl, LiBr or LiI, the Zr source is, for example, ZrCl4, the M source is, for example, the chloride of M, the Cl source is, for example, from at least one of the Li source, Zr source or M source, the Br source and the I source are, for example, from the Li source, the ball material mass ratio is, for example, (1 to 100): 1, the ball milling time is, for example, 1h to 72h, and the rotation speed is, for example, 100rpm to 1500rpm. After obtaining the first electrolyte, the first solid electrolyte layer 131 is prepared by, for example, a powder extrusion molding method, a wet coating method or an electrostatic spraying method.
[0034] See also Figure 2As shown, in one embodiment of the present invention, when the first solid electrolyte layer 131 is prepared by powder extrusion molding, the first electrolyte and the first binder are firstly mixed evenly, for example, by low-temperature shear mixing, and then the mixture is rapidly heated up for high-temperature shear mixing to obtain a mixture, and then the mixture is added to a roller press for high-temperature rolling to obtain the first solid electrolyte layer 131. Among them, the first binder is, for example, selected from at least one of PTFE, ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-trifluorochloroethylene copolymer, the content of the first electrolyte in the mixed material is, for example, 95wt% to 99.9wt%, the content of the first binder in the mixed material is, for example, 0.1wt% to 5wt%, the temperature of low-temperature shearing is, for example, -30℃ to 15℃, the temperature of high-temperature shearing is, for example, 20℃ to 200℃, and the temperature of high-temperature rolling is, for example, 20℃ to 200℃.
[0035] See also Figure 1As shown, in another embodiment of the present invention, when the first solid electrolyte layer 131 is prepared by wet coating or electrostatic spraying, the first electrolyte, the second binder and the solvent are firstly mixed evenly to obtain a mixed component, and then the mixed component is coated on the substrate by wet coating or electrostatic spraying, and then the substrate coated with the mixed component is dried at high temperature and peeled off to obtain the first solid electrolyte layer 131. The second binder is, for example, selected from PVDF, carboxymethyl cellulose ((Carboxymethyl Cellulose, CMC), styrene butadiene rubber (Polymerized Styrene Butadiene Rubber, SBR), polyvinyl pyrrolidone (Polyvinyl pyrrolidone, PVP), polymethyl methacrylate (Polymethyl Methacrylate, PMMA), polyacrylonitrile (Polyacrylonitrile, PAN), polyacrylic acid (Polyacrylic acid, PAA), polyurethane, polyvinyl alcohol (Polyvinyl alcohol, PVA), sodium alginate (Sodium alginate, Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, polyvinylidene fluoride, fluororubber, β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer, etc., the solvent is selected from toluene, chlorobenzene, xylene, dimethyl carbonate, N- At least one of methylformamide, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethanedithiol, acetonitrile, tetrahydrofuran, methanol, isopropyl ether, acetone, hexene, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone, etc., the content of the first electrolyte in the mixed component is 30wt% to 90wt%, the content of the second binder in the mixed component is, for example, 0.1wt% to 10wt%, the content of the solvent in the mixed component is, for example, 10wt% to 50wt%, the substrate is, for example, selected from polyethylene glycol terephthalate (PET) film, smooth aluminum foil or release paper, and the temperature of high-temperature drying is, for example, 30°C to 250°C.
[0036] See also Figure 1 As shown, in one embodiment of the present invention, the second solid electrolyte layer 132 includes a second electrolyte, and the second electrolyte is, for example, a sulfide electrolyte, which can further improve the lithium ion conductivity and electrochemical redox stability of the second solid electrolyte layer 132 and the solid electrolyte membrane 13. Specifically, the chemical formula of the second electrolyte is, for example, selected from Lia P 1- b T b S c O d X e or Li f P 1-g E g S w O g Q z at least one of etc. Among them, in Li a P 1-b T b S c O d X e Among them, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, T is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V or Nb, etc. X is selected from at least one of Cl, Br or I, etc. Further, T is selected from at least one of Sb, In or Bi, etc. X is, for example, Cl, and the value range of b is 0 < b ≤ 0.1. More specifically, when M is, for example, a +5 valence element, b is, for example, 0.04, and when M is, for example, a +3 valence element, b is, for example, 0.02. By controlling the type of M element, the type of T element and the value range of b in the second electrolyte, the cycle performance of the all-solid-state battery 10 can be improved, thereby extending the service life of the battery.
[0037] Please refer to Figure 1 As shown, in an embodiment of the present invention, when the chemical formula of the second electrolyte is Li f P 1-g E g S w O g Q z Among them, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, etc. Q is selected from at least one of Cl, Br or I, etc. Further, E is, for example, Mg, Q is, for example, Cl, and the value range of g is 0.01 ≤ g ≤ 0.1. Specifically, g is, for example, 0.02. By controlling the type of E element, the type of Q element and the value range of g in the second electrolyte, the cycle performance of the all-solid-state battery 10 can be improved, thereby extending the service life of the battery.
[0038] Please refer to Figure 1 As shown, in an embodiment of the present invention, when preparing the second solid electrolyte layer 132, first, in an atmosphere of an inert gas such as argon, according to the chemical formula of the second electrolyte Lia P 1-b T b S c O d X e or Li f P 1-g E g S w O g Q z , after the Li source, P source, T source, S source and X source, or the Li source, P source, E source, S source and Q source are uniformly mixed according to the stoichiometric ratio, for example, they are placed in a ball mill for ball milling to obtain a precursor powder, and then the precursor powder is subjected to high temperature annealing and sintering to obtain a second electrolyte. Wherein, the Li source is, for example, selected from at least one of Li2S, LiCl, LiBr or LiI, the P source is, for example, P2S5, the T source is, for example, an oxide of T, the S source is, for example, from at least one of the Li source or P source, the X source is, for example, from the Li source, the E source is, for example, an oxide of E, the Q source is, for example, from the Li source, the ball material mass ratio is, for example, (1 to 100): 1, the ball milling time is, for example, 1h to 48h, the rotation speed is, for example, 50rpm to 1500rpm, the sintering temperature is, for example, 400℃ to 600℃, and the sintering time is, for example, 1h-48h. After obtaining the second electrolyte, the second solid electrolyte layer 132 is prepared, for example, by powder extrusion molding, wet coating, or electrostatic spraying. The process of preparing the second solid electrolyte layer 132 by powder extrusion molding, wet coating, or electrostatic spraying is the same as the process of preparing the first solid electrolyte layer 131 by powder extrusion molding, wet coating, or electrostatic spraying, and is not further elaborated here.
[0039] See also Figure 1 As shown, in one embodiment of the present invention, when preparing the solid electrolyte membrane 13 , the first solid electrolyte layer 131 and the second solid electrolyte layer 132 are rolled to form the solid electrolyte membrane 13 .
[0040] See also Figure 1 As shown, in one embodiment of the present invention, the above-mentioned positive electrode 11, solid electrolyte membrane 13 and negative electrode 12 are sequentially stacked, packaged, hot pressed and cold pressed to assemble into an all-solid-state battery 10.
[0041] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0042] Example 1
[0043] Preparation of the first electrolyte: 1.35 mol of LiCl, 0.5 mol of LiBr, 0.5 mol of LiI, 0.65 mol of ZrCl4 and 0.35 mol of FeCl3 were subjected to high-energy ball milling under an argon atmosphere to prepare Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 Electrolyte materials.
[0044] Preparation of the second electrolyte: 2 mol of Li2S, 1.5 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 were subjected to high-energy ball milling under an argon atmosphere to prepare Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The precursor powder was sintered at 500 °C for 10 h and then cooled to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Electrolyte materials.
[0045] Preparation of the first solid electrolyte layer: Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The electrolyte material and PTFE were mixed at a mass ratio of 99:1 at -20°C, and the temperature was raised to 80°C to mix the PTFE to fiberize the first solid electrolyte layer. 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 &PTFE mixed material. Then Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The PTFE mixed material was extruded into a roller press, and the electrolyte membrane was rolled to a thickness of 5 μm at 80°C by adjusting the roller press gap to form the first solid electrolyte layer.
[0046] Preparation of the second solid electrolyte layer: Li 5.5 P 0.96 Sb 0.04 S 4.40 O0.10 Cl 1.5 The electrolyte material and PTFE were mixed evenly at a mass ratio of 99:1 at -20°C, and the temperature was raised to 80°C to mix the PTFE to fiberize the second solid electrolyte layer. 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 &PTFE mixed material. Then Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The PTFE mixed material is extruded into a roller press, and the electrolyte membrane is rolled to a thickness of 5 μm at 80°C by adjusting the roller press gap to form a second solid electrolyte layer.
[0047] Preparation of solid electrolyte membrane: The first solid electrolyte layer and the second solid electrolyte layer are rolled and compounded into a solid electrolyte membrane in a roller press.
[0048] Preparation of positive electrode: The positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O2, the chemical formula of the halide solid electrolyte is Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The conductive agent includes SuperP and VGCF, and the mass ratio of SuperP and VGCF is, for example, 1:1, and the binder is, for example, PTFE. The positive electrode active material, the halide solid electrolyte, the conductive agent and the binder are uniformly mixed in a mass ratio of, for example, 69:29:1:1, and the positive electrode is obtained by dry pressing.
[0049] Choice of negative electrode: Choose metallic lithium as the negative electrode.
[0050] Battery preparation: The positive electrode, solid electrolyte membrane and negative electrode are stacked, packaged, hot pressed and cold pressed in sequence to assemble into an all-solid-state soft-pack battery.
[0051] Example 2
[0052] The difference between this embodiment and embodiment 1 is that the thickness of the second solid electrolyte layer is adjusted to 25 μm by adjusting the roller gap of the roller press.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that the thickness of the second solid electrolyte layer is adjusted to 50 μm by adjusting the roller gap of the roller press.
[0055] Example 4
[0056] The difference between this embodiment and embodiment 1 is that the thickness of the second solid electrolyte layer is adjusted to 150 μm by adjusting the roller gap of the roller press.
[0057] Example 5
[0058] The difference between this embodiment and embodiment 2 is that the thickness of the first solid electrolyte layer is adjusted to 1 μm by adjusting the roller gap of the roller press.
[0059] Example 6
[0060] The difference between this embodiment and embodiment 2 is that the thickness of the first solid electrolyte layer is adjusted to 50 μm by adjusting the roller gap of the roller press.
[0061] Example 7
[0062] The difference between this embodiment and embodiment 2 is that the thickness of the first solid electrolyte layer is adjusted to 100 μm by adjusting the roller gap of the roller press.
[0063] Example 8
[0064] The difference between this embodiment and embodiment 2 is that the chemical formula of the first solid electrolyte layer is Li 2.2 Zr 0.8 Fe 0.2 Cl5Br 0.5 I 0.5 The raw materials are 1.2 mol LiCl, 0.5 mol LiBr, 0.5 mol LiI, 0.8 mol ZrCl4 and 0.2 mol FeCl3.
[0065] Example 9
[0066] The difference between this embodiment and embodiment 2 is that the chemical formula of the first solid electrolyte layer is Li 2.6 Zr 0.4 Fe 0.6 Cl5Br 0.5 I 0.5 The raw materials are 1.6 mol of LiCl, 0.5 mol of LiBr, 0.5 mol of LiI, 0.4 mol of ZrCl4 and 0.6 mol of FeCl3.
[0067] Example 10
[0068] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.5 P 0.99 Sb 0.01 S 4.475 O 0.025 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of Sb2O5.
[0069] Embodiment 11
[0070] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.5 P 0.94 Sb 0.06 S 4.35 O 0.15 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Sb2O5.
[0071] Example 12
[0072] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.5 P 0.9 Sb 0.1 S 4.25 O 0.25 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Sb2O5.
[0073] Embodiment 13
[0074] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.1 P 0.96 Sb 0.04 S4O 0.10 Cl 1.9 The raw materials are 1.6 mol of Li2S, 1.9 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5.
[0075] Embodiment 14
[0076] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.9 P 0.96 Sb 0.04 S 4.80 O 0.10Cl 1.1 The raw materials are 2.4 mol of Li2S, 1.1 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5.
[0077] Embodiment 15
[0078] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.4 Br 0.1 The raw materials are 2 mol of Li2S, 1.4 mol of LiCl, 0.1 mol of LiBr, 0.48 mol of P2S5 and 0.02 mol of Sb2O5.
[0079] Example 16
[0080] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.48 mol of P2S5 and 0.02 mol of Sb2O5.
[0081] Embodiment 17
[0082] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.52 P 0.99 In 0.01 S 4.485 O 0.015 Cl 1.5 The raw materials are 2.01 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of In2O3.
[0083] Embodiment 18
[0084] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl1.5 The raw materials are 2.02 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of In2O3.
[0085] Embodiment 19
[0086] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.62 P 0.94 In 0.06 S 4.41 O 0.09 Cl 1.5 The raw materials are 2.06 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of In2O3.
[0087] Embodiment 20
[0088] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 The raw materials are 2.1 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of In2O3.
[0089] Embodiment 21
[0090] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.14 P 0.98 In 0.02 S 4.07 O 0.03 Cl 1.9 The raw materials are 1.62 mol of Li2S, 1.9 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of In2O3.
[0091] Embodiment 22
[0092] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.94 P 0.98 In 0.02 S 4.87 O 0.03 Cl 1.1 The raw materials are 2.42 mol of Li2S, 1.1 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of In2O3.
[0093] Embodiment 23
[0094] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.4 Br 0.1 The raw materials are 2.02 mol of Li2S, 1.4 mol of LiCl, 0.1 mol of LiBr, 0.49 mol of P2S5 and 0.01 mol of In2O3.
[0095] Embodiment 24
[0096] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2.02 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.49 mol of P2S5 and 0.01 mol of In2O3.
[0097] Embodiment 25
[0098] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.52 P 0.99 Bi 0.01 S 4.485 O 0.015 Cl 1.5 The raw materials are 2.01 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of Bi2O3.
[0099] Embodiment 26
[0100] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.5 The raw materials are 2.02 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.
[0101] Embodiment 27
[0102] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.62 P 0.94 Bi 0.06 S 4.41 O 0.09 Cl 1.5 The raw materials are 2.06 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Bi2O3.
[0103] Embodiment 28
[0104] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 The raw materials are 2.1 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Bi2O3.
[0105] Embodiment 29
[0106] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.14 P 0.98 Bi 0.02 S 4.07 O 0.03 Cl 1.9 The raw materials are 1.62 mol of Li2S, 1.9 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.
[0107] Embodiment 30
[0108] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.94 P 0.98 Bi 0.02 S 4.87 O 0.03 Cl 1.1 The raw materials are 2.42 mol of Li2S, 1.1 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.
[0109] Embodiment 31
[0110] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.4 Br 0.1 The raw materials are 2.02 mol of Li2S, 1.4 mol of LiCl, 0.1 mol of LiBr, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.
[0111] Embodiment 32
[0112] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2.02 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.
[0113] Embodiment 33
[0114] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.53 P 0.99 Mg 0.01 S 4.49 O 0.01 Cl 1.5 The raw materials are 2.015 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.01 mol of MgO.
[0115] Embodiment 34
[0116] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.5 The raw materials are 2.03 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.02 mol of MgO.
[0117] Embodiment 35
[0118] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li5.68 P 0.94 Mg 0.06 S 4.44 O 0.06 Cl 1.5 The raw materials are 2.09 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.06 mol of MgO.
[0119] Embodiment 36
[0120] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 The raw materials are 2.15 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.1 mol of MgO.
[0121] Embodiment 37
[0122] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.16 P 0.98 Mg 0.02 S 4.08 O 0.02 Cl 1.9 The raw materials are 1.83 mol of Li2S, 1.9 mol of LiCl, 0.49 mol of P2S5 and 0.02 mol of MgO.
[0123] Embodiment 38
[0124] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 6.96 P 0.98 Mg 0.02 S 5.88 O 0.02 Cl 0.1 The raw materials are 3.43 mol of Li2S, 0.1 mol of LiCl, 0.49 mol of P2S5 and 0.02 mol of MgO.
[0125] Embodiment 39
[0126] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.4 Br0.1 The raw materials are 2.03 mol of Li2S, 1.4 mol of LiCl, 0.1 mol of LiBr, 0.49 mol of P2S5 and 0.02 mol of MgO.
[0127] Embodiment 40
[0128] The difference between this embodiment and embodiment 2 is that the chemical formula of the second solid electrolyte layer is Li 5.56 P 0.98 Mg 0.02 S 4.48 O 0.02 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2.03 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.49 mol of P2S5 and 0.02 mol of MgO.
[0129] Embodiment 41
[0130] The difference between this embodiment and embodiment 2 is that during the preparation of the first solid electrolyte layer and the second solid electrolyte layer, ETFE is selected as the first binder.
[0131] Embodiment 42
[0132] The difference between this embodiment and embodiment 2 is that during the preparation of the first solid electrolyte layer and the second solid electrolyte layer, PCTFE is selected as the first binder.
[0133] Embodiment 43
[0134] The difference between this embodiment and embodiment 2 is that the first solid electrolyte layer and the second solid electrolyte layer are prepared by a wet coating method.
[0135] Specifically, the first solid electrolyte layer is prepared by: 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The electrolyte material, SBR binder and xylene solvent were mixed uniformly in a mass ratio of 49:1:50 to obtain a mixed component, and the mixed component was scraped onto a smooth aluminum foil using a 5 μm film applicator and vacuum dried at 80 °C to prepare a 5 μm thick Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 A first solid electrolyte layer.
[0136] Preparation of the second solid electrolyte layer: Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The electrolyte material, SBR binder and xylene solvent were mixed uniformly in a mass ratio of 49:1:50 to obtain a mixed component, and the mixed component was scraped onto a smooth aluminum foil using a 25 μm film applicator and vacuum dried at 80 °C to prepare a 25 μm thick Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 A second solid electrolyte layer.
[0137] Embodiment 44
[0138] The difference between this embodiment and Embodiment 43 is that during the preparation of the first solid electrolyte layer and the second solid electrolyte layer, PVDF is selected as the second binder.
[0139] Embodiment 45
[0140] The difference between this embodiment and Embodiment 43 is that during the preparation of the first solid electrolyte layer and the second solid electrolyte layer, PAA is selected as the second binder.
[0141] Comparative Example 1
[0142] The difference between this comparative example and Example 2 is that the chemical formula of the second solid electrolyte layer is Li 5.5 PS 4.5 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl and 0.5 mol of P2S5.
[0143] Comparative Example 2
[0144] The difference between this comparative example and Example 2 is that the solid electrolyte membrane only includes the first solid electrolyte layer.
[0145] Comparative Example 3
[0146] The difference between this comparative example and Example 2 is that the solid electrolyte membrane only includes the second solid electrolyte layer.
[0147] Comparative Example 4
[0148] The difference between this comparative example and Example 2 is that the thickness of the first solid electrolyte layer is adjusted to 5 μm and the thickness of the second solid electrolyte layer is adjusted to 1 μm by adjusting the roller gap of the roller press.
[0149] The compositions and parameters of the first solid electrolyte layer and the second solid electrolyte layer in each embodiment and comparative example are shown in Table 1.
[0150] Table 1. Composition of the first solid electrolyte layer and the second solid electrolyte layer in Examples 1 to 45 and Comparative Examples 1 to 4
[0151]
[0152]
[0153]
[0154] In the present invention, performance tests were performed on all-solid-state batteries prepared using different solid electrolyte membranes in Examples 1 to 45 and Comparative Examples 1 to 4.
[0155] See also Figure 3 As shown, in one embodiment of the present invention, the morphology of the solid electrolyte membrane in Example 2 is characterized by, for example, a scanning electron microscope. The magnification of the scanning electron microscope is, for example, 10,000 times. Figure 3 It can be seen that the first solid electrolyte layer and the second solid electrolyte layer prepared by the powder extrusion molding method have good self-supporting properties and can stably exist between the positive electrode and the negative electrode, thereby facilitating better performance of the solid electrolyte membrane.
[0156] See also Figure 4 As shown, in one embodiment of the present invention, for example, the all-solid-state battery in Example 3 is subjected to a room temperature cycle performance test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V to obtain the capacity (CC) and coulombic efficiency (CE) at different cycle numbers. Figure 4 It can be seen that with the increase in the number of cycles, the attenuation trend of the battery capacity is relatively gentle, and the coulombic efficiency of the battery does not fluctuate and stabilizes at around 100%, which indicates that the battery has good cycle performance.
[0157] Please refer to Table 2. In one embodiment of the present invention, for example, the all-solid-state batteries in Examples 1 to 45 and Comparative Examples 1 to 4 are subjected to a room temperature cycle stability test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V. The test is terminated when the battery capacity reaches 80% of the first cycle capacity State of Health (SOH), and the number of room temperature cycles of the battery is recorded. The recorded results are shown in Table 2.
[0158] Table 2. Test results of all-solid-state batteries in Examples 1 to 45 and Comparative Examples 1 to 4
[0159]
[0160]
[0161] Please refer to Table 1 and Table 2. By comparing Example 2, Comparative Example 2 and Comparative Example 3, it can be seen that if the first solid electrolyte layer is used alone as the solid electrolyte membrane, the battery will soon short-circuit and have almost no cycle performance. If the second solid electrolyte layer is used alone as the solid electrolyte membrane, the number of normal temperature cycles of the battery is only 493. However, if the first solid electrolyte layer and the second solid electrolyte layer are combined as the solid electrolyte membrane, the number of normal temperature cycles of the battery increases to 1394, indicating that in the solid electrolyte membrane formed by stacking the first solid electrolyte layer and the second solid electrolyte layer, the first electrolyte in the first solid electrolyte layer can match the positive electrode, and the second electrolyte in the second solid electrolyte layer can provide high lithium ion conductivity and good electrochemical redox stability, thereby improving the cycle performance of the battery.
[0162] Please refer to Table 1 and Table 2. By comparing Examples 1 to 4 and Comparative Example 4, it can be seen that as the thickness of the second solid electrolyte layer increases from 5 μm to 150 μm, the number of normal temperature cycles of the battery first increases gradually and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Moreover, when the thickness of the second solid electrolyte layer is as thin as 1 μm, a battery short circuit occurs. Therefore, by controlling the thickness of the second solid electrolyte layer, the cycle performance of the battery can be improved.
[0163] As shown in Table 1 and Table 2, by comparing Example 2 with Examples 5 to 7, it can be seen that as the thickness of the first solid electrolyte layer increases from 1 μm to 100 μm, the number of normal temperature cycles of the battery first increases gradually and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the thickness of the first electrolyte layer, the cycle performance of the battery can be improved.
[0164] Please refer to Table 1 and Table 2. By comparing Example 2 with Examples 8 to 9, it can be seen that as the doping amount of the Fe element in the first solid electrolyte layer increases, the ionic conductivity of the first solid electrolyte layer first increases and then decreases, and at the same time, the number of normal temperature cycles of the battery first increases gradually and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, in the first solid electrolyte layer, by controlling the doping amount of the M element in the first electrolyte, the cycle performance of the battery can be improved.
[0165] Please refer to Table 1 and Table 2. By comparing Example 2 and Examples 10 to 12, it can be seen that as the doping amount of the Sb element in the second solid electrolyte layer increases, the ionic conductivity of the second solid electrolyte layer gradually decreases, and the number of normal temperature cycles of the battery first increases gradually, and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. By comparing Examples 17 to 20, it can be seen that as the doping amount of the In element in the second solid electrolyte layer increases, the ionic conductivity of the second solid electrolyte layer gradually decreases, and the number of normal temperature cycles of the battery first increases gradually, and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. By comparing Examples 25 to 28, it can be seen that as the doping amount of the Bi element in the second solid electrolyte layer increases, the ionic conductivity of the second solid electrolyte layer gradually decreases, and the number of normal temperature cycles of the battery first increases gradually, and then decreases gradually, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, in the second solid electrolyte layer, by controlling the doping amount of the T element in the second electrolyte, the cycle performance of the battery can be improved.
[0166] As shown in Table 1 and Table 2, it can be seen from the comparison of Examples 33 to 36 that as the doping amount of the Mg element in the second solid electrolyte layer increases, the ionic conductivity of the second solid electrolyte layer gradually decreases, and the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, in the second solid electrolyte layer, by controlling the doping amount of the E element in the second electrolyte, the cycle performance of the battery can be improved.
[0167] Refer to Table 1 and Table 2, and compare Examples 2, 13 and 14, Examples 18, 21 and 22, Examples 26, 29 and 30, and Examples 34, 37 and 38. It can be seen that when the doping amount of Sb, In, Bi or Mg in the second solid electrolyte layer is the same, if one second electrolyte molecule contains 1.5 Cl atoms, the number of normal temperature cycles of the battery reaches the maximum. On the contrary, if the number of Cl atoms in one second electrolyte molecule is higher or lower than 1.5, the number of normal temperature cycles of the battery will decrease, that is, the cycle performance of the battery is reduced. Therefore, in the second solid electrolyte layer, by controlling the doping amount of X or Q element in the second electrolyte, the cycle performance of the battery can be improved.
[0168] Refer to Table 1 and Table 2. By comparing Examples 2, 15 and 16, Examples 18, 23 and 24, Examples 26, 31 and 32, and Examples 34, 39 and 40, it can be seen that when the doping amount of Sb, In, Bi or Mg in the second solid electrolyte layer is the same, if one or more of Br or I is doped into the second solid electrolyte layer, the ionic conductivity of the second solid electrolyte layer will decrease, and the number of normal temperature cycles of the battery will also decrease, that is, the cycle performance of the battery will be reduced. Therefore, in the second solid electrolyte layer, by controlling the number of element types contained in X or Q in the second electrolyte, the cycle performance of the battery can be improved.
[0169] Please refer to Table 1 and Table 2. By comparing Example 18, Example 26, Example 34 and Comparative Example 1, it can be seen that when the second solid electrolyte layer is not doped with Sb, In, Bi or Mg elements, the ionic conductivity of the second solid electrolyte layer will increase, but the battery will soon short-circuit and have almost no cycle performance, indicating that the Sb, In, Bi or Mg elements doped in the second solid electrolyte layer can significantly improve the cycle performance of the battery. Therefore, in the second solid electrolyte layer, by controlling the type of T or E elements in the second electrolyte, the cycle performance of the battery can be improved.
[0170] As shown in Table 1 and Table 2, by comparing Example 2, Example 41 and Example 42, it can be seen that the first binder used in the preparation process of the first solid electrolyte layer and the second solid electrolyte layer is different, resulting in different ionic conductivities of the first solid electrolyte layer and the second solid electrolyte layer, and also resulting in different cycle performances of the battery. Specifically, when PTFE is used as the first binder, the number of normal temperature cycle cycles of the battery is the largest, that is, the cycle performance of the battery is the best.
[0171] Please refer to Table 1 and Table 2. By comparing Example 2 and Examples 43 to 45, it can be seen that the preparation methods of the first solid electrolyte layer and the second solid electrolyte layer are different, resulting in different ionic conductivities of the first solid electrolyte layer and the second solid electrolyte layer, and also resulting in different cycle performances of the battery. Specifically, compared with the wet coating method, the first solid electrolyte layer and the second solid electrolyte layer prepared by the powder extrusion molding method have the largest ionic conductivity, and the number of room temperature cycles of the assembled battery is also the largest, that is, the cycle performance is the best.
[0172] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state batteries, and the all-solid-state battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state battery, and therefore includes the advantages of the above-mentioned all-solid-state battery, which will not be elaborated here.
[0173] In summary, the present invention proposes an all-solid-state battery and its application. By compounding a first solid electrolyte layer and a second solid electrolyte layer, a high-voltage resistant heterogeneous self-supporting solid electrolyte membrane is prepared, which can make the solid electrolyte membrane have the advantage of high lithium ion conductivity, thereby improving the working efficiency of the battery. At the same time, the electrochemical redox stability of the solid electrolyte membrane can be improved, so that the electrolyte can effectively resist the problems of redox reaction and electrode interface instability. At the same time, the electrochemical window of the solid electrolyte membrane can be widened, so that the solid electrolyte membrane can adapt to high-voltage positive electrodes such as lithium-rich manganese or lithium nickel manganese oxide, thereby improving the stability of the battery. Moreover, the first solid electrolyte layer and the second solid electrolyte layer can improve the cycle performance of the battery and extend the service life of the battery.
[0174] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0175] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. An all-solid-state battery, characterized in that: At least: The first solid electrolyte layer is arranged on the positive electrode side of the all-solid-state battery, and the ion conductivity of the first solid electrolyte layer is 1×10 -4 S / cm~1×10 -2 S / cm; and The second solid electrolyte layer is arranged on the negative electrode side of the all-solid-state battery, and the ion conductivity of the second solid electrolyte layer is 1×10 -3 S / cm~2×10 -2 S / cm.
2. The all-solid-state battery according to claim 1, characterized in that: The first solid electrolyte layer includes a first electrolyte, the chemical formula of which is Li 2+n Zr 1-n M n Cl 6-x-y Br x I y , wherein 0≤n≤0.6, 0≤x≤6, 0≤y≤6, x+y≤6, and M is selected from at least one of V, Cr, Mn, Fe, Co and Ni.
3. The all-solid-state battery according to claim 2, characterized in that: M is Fe, and the value range of n is 0.01≤n≤0.
5.
4. The all-solid-state battery according to claim 1, characterized in that: The second solid electrolyte layer includes a second electrolyte, and the chemical formula of the second electrolyte is Li a P 1-b T b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, T is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V or Nb, and X is selected from at least one of Cl, Br or I.
5. The all-solid-state battery according to claim 4, characterized in that: T is selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is 0 <b≤0.1。 6. The all-solid-state battery according to claim 1, characterized in that: The second solid electrolyte layer includes a second electrolyte, and the chemical formula of the second electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from at least one of Cl, Br or I.
7. The all-solid-state battery according to claim 6, characterized in that: E is Mg, Q is Cl, and the value range of g is 0.01≤g≤0.
1.
8. The all-solid-state battery according to claim 1, characterized in that: The thickness of the first solid electrolyte layer is 1 μm to 100 μm.
9. The all-solid-state battery according to claim 1, characterized in that: The thickness of the second solid electrolyte layer is 5 μm to 150 μm.
10. An electronic device, characterized in that: An all-solid-state battery comprising any one of claims 1 to 9.
